The role of university sports federations in enhancing student sports : a comparative case study between Portugal and Finland - Yandjou, Patrick (2011)
The European Union has increasingly emphasized the sociological, physiological and psychological benefits of sport. Sport provision and participation trends have been measured throughout the member-states and, the gaps between Northern and Southern countries are widely acknowledged. These gaps are especially wide between young-adults and the elderly. The integration of sports into the education curriculum in most European pedagogic systems has resulted in high levels of sport practice among the youth. However as young people enter higher education, member-states face a problem with a natural withdrawal in participation. The universities and student sports federations can plan an important role in reversing this phenomenon. Therefore, it is crucial to understand the role of university sports federations.